Literary text reading and conversation: beyond ethnomethodology boundaries (2014)
This article leaves aside ethnomethodological approaches to conversation, and aims at opening the debate about the need of conceiving it under the light of pedagogical principles that position it as a propitious discursive gender to express the emotional, aesthetics, thoughtful, and intellectual meetings embodied while reading literary texts. Such interest arose from a research centered on finding the existing relationships between conversation and construction of aesthetical-literary experiences. The results show that students get a pleasant feeling when giving sense to what they read, and this encourages them to share with others their significant experiences when reading, allowing the internal process of meaning construction and the dialogic strengthening of the experiences to be connected.